Nolite te bastardes carborundorum: discursos, poderes e resistências em The handmaid’s tale - Lima, Thainá da Costa (2022)
The handmaid's tale (or O conto da aia, in a Brazilian version) is an American television series of great success in Brazil. Based on the novel of the same name by canadian writer Margaret Atwood, originally published in 1985, the production was released in 2017 by the streaming service Hulu and presents a dystopian narrative that takes place in Gilead: a fictional place located in what would be the territory of the United States and where, after a coup d'état, a theocratic revolution is promoted. In the plot, which has already spanned four seasons (and which has been renewed for the fifth), Gilead presents a historical urgency linked to the low birth rate, a justification from which an entire device of power is organized – around the theocratic State – which not only takes rights away from women in general, but also sexually enslaves fertile women. Starting from this scenario and making use of photograms, this research has the objective of mapping the practices of power and resistance present, mainly, in the first season of the series, concretized within the device that organizes the relations of force in the narrative. It will therefore be a matter of identifying how such relationships are exercised over the bodies and lives of the characters, through technologies and techniques of sovereignty, disciplines and biopolitics. But beyond that, it will also be a matter of analyzing how such power relations produce places of resistance that emerge in social microspheres. As a theoretical-methodological contribution, we use the Foucaultian Discourse Analysis articulated with the discussion undertaken by Frédéric Gros (2018) around a stylistics of (dis)obedience.